The contagion of ideas. Social and conceptual practice, common sense (Altre Modernità, 2023)
The essay offers some insights into the ways in which some ideas arise, spread and consolidate themselves within a collectivity of people, with outcomes that are useful in fostering a sense of social cohesion. In parallel, it discusses the reasons why in certain cases a representation is contested, debated and generates conflicts and controversies, fostering a sense of uncertainty and social fragmentation.
Keywords: sense of belonging; aspirations; uncertainty; epidemiology of ideas